Human Resources Management in Businesses: The Case Of A Turkish Airline - Yılmaz, Rabia (Contemporary Business and Economic Issues II, 2023)
Human resources are one of the most needed resources by businesses established to meet human needs while fulfilling their production activities. HRM in organizations is a process arising from strategic necessity. The main purpose of this study is to examine the concept, scope, principles, and function of HRM. In addition, this study aims to determine how HRM practices are carried out in Pegasus Airlines, one of the most important airline companies in Turkey, and what kind of effects they create. Pegasus Airlines is also analyzed and evaluated in the context of the functions and the basic principles of HRM.